The Application of Uṣūl al-Fiqh (Principles of Islamic Jurisprudence) in Sharia Economics: Theoretical Review - Sutisna; Suci Purwati; Sitty Komalla (Islamicate Institute, 2023)
This theoretical study delves into the foundational concepts of Uṣūl al-Fiqh and their role as the theoretical framework underpinning Sharia economic principles. Through a qualitative approach involving a literature review, this study conducts an in-depth examination of these principles to foster the development of a Sharia economy characterized by inclusivity, fairness, and sustainability. This research advances Sharia economics rooted in Islamic values by offering more effective solutions to existing challenges. Furthermore, building upon this theoretical foundation, the study explores practical applications of Sharia economic principles, envisioning tangible solutions to real-world economic issues. By integrating insights from the theoretical inquiry into economic policies and practices, it becomes feasible to cultivate economic systems that adhere to Islamic values and promote equitable growth and societal well-being. In summary, this theoretical exploration catalyzes the development of a dynamic and progressive Sharia economy that aligns with Islamic ethics and contemporary economic realities.